Sexually transmitted infections on the border between Suriname and French Guiana: A scoping review - Nacher, Mathieu; Koendjbiharie, Aylosius; Michaud, Céline; Rabier, Sébastien; Leborgne, Cyril; Rousseau, Cyril; Lucarelli, Aude; Thorey, Camille; Gonzales, Adriana; Terlutter, Fredrik; Thomas, Nadia; Gastel, Benoit Van; et al. (Frontiers in Medicine, 2022)
Purpose. The Maroni basin –delineating the border between Suriname and French Guiana— presents sociocultural, geographical and economic circumstances that have been conducive to the circulation of sexually transmitted infections and to delays in diagnosis and care. Given the scarcity of published data, we aimed to describe different sexually transmitted infections along the Maroni and to gain a broader understanding of the epidemiologic situation. Methods We conducted a scoping review of the efforts to approach the problem of sexually transmitted infections in this complex border area. Temporal trends were plotted and crude numbers were divided by local population numbers. Results For HIV, despite increasing testing efforts, most patients still present at the advanced HIV stage (median CD4 count at diagnosis is <20 per mm3), and 25% of patients in Saint Laurent du Maroni were lost to follow-up within 6 years. However, progress on both sides has led to a decline in AIDS cases and mortality. Despite a rapid increase in the 1990’s along the Maroni, the current HIV prevalence seemed lower (0.52%) in the rural villages than in coastal urban centers (>1%). High risk HPV infection prevalence among women reaches 23.3% . The incidence of gonorrhea was 4.2 per 1000 population aged 15-59. For Chlamydia it was 3.4 per 1000 population aged 15-59. For syphilis, the incidence was 2.5 per 1000 population aged 15- 59. Gonorrhea, Chlamydia, hepatitis B detection increased over time with greater testing efforts and new diagnostic tests. Since the COVID-19 epidemic, congenital syphilis has dramatically increased in Saint Laurent du Maroni reaching 808 per 100,000 live births. Conclusions Sexually transmitted infections seemed more prevalent in Saint Laurent du Maroni –the sole urban center—than in the remote villages along the Maroni. The syndromic approach and the heterogeneity of diagnostic platforms presumably overlook most infections in the region, therefore concerted approach and a shared diagnostic upgrade with molecular diagnosis and rapid diagnostic tests seem necessary to reduce the burden of sexually transmitted infections on both sides of the Maroni. Congenital syphilis resulting from COVID-19 disruption of Health services requires urgent attention.